Perilaku Konsumtif Santri Blok E Pondok Pesantren Nurul Qarnain dalam Pandangan Al-Ghazali - Halili, Halili (Maisyatuna, 2023)
Pondok Pesantren Nurul Qarnain is a pesantren with approximately 3000 students. 65% of these students are students with junior high education who are sitting in Madrasah Tsanawiyah (MTS) and Madrasah Diniyah Muadalah Tsanawiyah (MDMT), in other words more than half of the total number of students are children aged 12 to 15 years. Santri, who have just entered adolescence, seem to have difficulty distinguishing between primary, secondary and tertiary needs so that in some findings their consumption behavior tends to be wasteful. This study aims to look fully at how the consumption behavior of students aged 12 years to 15 years who are in the Block E dormitory environment in the view of Imam Al-Ghazali considering that the dormitory is the location of the basic level of yellow book learning at Nurul Qarnain Islamic Boarding School. This research is a phenomenological qualitative research because the type of data explored in the form of information, comments, opinions, or sentences about the phenomenon of consumptive behavior of students of Madrasah Diniyah Mu'is Tsanawiyah Nurul Qarnain Jember Islamic Boarding School, not the views of researchers. First, consumption behavior has three levels or levels of needs, namely: the needs of daruriyat (primary), hajiyat (secondary) and tahsiniyat (tertiary). Second, students of Madrasah Diniyah Muadalah Tsanawiyah in fulfilling their needs give more priority to primary needs, this can be seen from their behavior in meeting school needs such as stationery and uniforms, bathing and washing needs, and paying tuition fees. Secondary needs are met by laundry uniforms by some students who are afraid of being switched, besides that other students prefer to be careful so that uniforms are not lost or switched. The tertiary needs of students are met when they have clothes or supporting products such as perfume and handbody.